Work-Life Balance Benefit: Organizational Commitment and Retention of Female Employees in SMEs Company in Perlis - Hafsah, Wahab (2012)
This study explores the relatioinship between work-life balance/family friendly benefit and organizational commitment/attachment and retention among one private company in Perlis, Malaysia. In this study, two independent variables namely organizational commitment/attachment and retention were tested against work-life balance/family friendly benefit. 70 female employees as respondents participated in this study. The research objectives were answered using correlation and regression analysis. The results are also presented using descriptive statistics. However, no relationship was found between organizational commitment/attachment and retention and the details were discussed in this study. Suggestions were made for further research to broader participants in private and government sector and also specifically to female employees from generation X and Y.